Diagnosis of pulmonary hypertension using spectral-detector CT. (15th June 2019) - Kröger, Jan Robert; Gerhardt, Felix; Dumitrescu, Daniel; Rosenkranz, Stephan; Schmidt, Matthias; Maintz, David; Bunck, Alexander C.
Abstract: Objectives: To evaluate the value of spectral-detector CT (SDCT) in the diagnosis of chronic thromboembolic pulmonary hypertension (CTEPH), its differentiation against other etiologies of pulmonary hypertension (PH) and in the prediction of disease severity. Materials and methods: 60 patients with suspected PH underwent SDCT. Additional diagnostic tests in accordance with the ESC guidelines including right heart catherization and VQ-SPECT were performed. After full diagnostic work-up patients were classified as: 21 precapillary PH, 5 postcapillary PH, 6 combined pre- and postcapillary PH, 19 CTEPH, 9 no PH. SDCT examinations were analyzed by two blinded readers deciding on the diagnosis of CTEPH and scoring the extent of perfusion abnormalities on iodine density images. An additional reading was performed using conventional CTPA images only. Results: With access to SDCT data, both readers reached a sensitivity of 100% for the diagnosis of CTEPH with a specificity of 95.1% and 87.8%. On analysis of conventional CTPA images alone, specificity and diagnostic confidence decreased for both readers (Specificity 90.2 and 85.3%) while sensitivity dropped for the less experienced reader only (Sensitivity 78.9%). Patients with PH showed significantly more perfusion abnormalities than patients without PH (16.6 ± 8.4 vs. 9.5 ± 8.9 p < 0.001) and the extent of perfusion abnormalities correlated with the mean pulmonary artery pressure (r = 0.37 p = 0.008). Conclusions: SDCT offers confident identification of patients with CTEPH and enables a comprehensive analysis of pulmonary vasculature, pulmonary perfusion and the lung parenchyma in a single examination for patients with suspected PH. Highlights: Spectral detector CT is valuable tool in the diagnostic work-up of PH. Spectral detector CT differentiates CTEPH from PH of other causes. SDCT/DECT has the potential to make V/Q-Scintigraphy obsolete for diagnosis of CTEPH.